The Meaning of Coins for the People of Tarempa Village, Anambas Islands Regency - Rizki Aprileo; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
The main problem of this research is to find out the meaning of coins for the people in Tarempa Village, Anambas Regency. In trading activities that occur in people's daily lives, the use of money is the most important thing. For most members of the community, money in any form will be valued and accepted in buying and selling transactions. However, this does not apply to the people of Anambas Regency, including those in Tarempa Village, as they refuse to use coins in their transactions. This study used a qualitative descriptive approach and collected data through interviews, observation, and documentation. The informants were selected using purposive sampling technique based on predetermined criteria. The data obtained were analyzed and conclusions were drawn. The results of the study indicate that people in Tarempa Village interpret coins as a form of money that is worthless, and therefore have no value in everyday transactions. Based on the theory of symbolic interactionism, this meaning can arise because of the exchange of symbols that occur. This act of refusal is the community's response to the given stimulus based on their habit.